Research and Academic Work Made Easy (KULT_online, 2013)
Undergraduate and advanced students of Romance studies searching for information about how to find scientific literature via electronic and printed resources are strongly advised to consult Ulrike Hollender's introductory volume "Erfolgreich recherchieren – Romanistik”. Using concrete examples, this volume explains clearly, precisely, and understandably the functionality of different information resources which on the one hand are subdivided according to the level of studies and on the other according to the Romance languages and the disciplines. Furthermore, text boxes draw the reader's attention to important supplementary information and advice. The volume also provides the reader with detailed information about how to obtain the literature one has found via the resources, how to evaluate its quality and relevance, and how to quote it correctly in written papers. Although this volume contains more than its title suggests, it always maintains its clear structure, which makes it a worthwhile acquisition.